Is maxillary diastema an appropriate site for implantation in rats? - Gang Yue; Husham Edani; Andrew Sullivan; Shuying Jiang; Hamed Kazerani; Mohammad Ali Saghiri (SpringerOpen, 2020)
Abstract Background Implantology or implant dentistry is growing fast during last four decades. Facing the growing demand of implant treatment, there are extreme challenges to clinicians and researchers. First is peri-implantitis with remarkable prevalence. Though investigators have revealed that the etiology of the peri-implant infection is similar to periodontitis, clinically there is no effective treatment. Second, implantation in patients with severe systemic conditions, i.e., severe diabetes, lupus, osteoporosis, organ transplant, and cancer with intensive radiotherapy and/or chemotherapy, is another challenge to implant treatment for lack of scientific research data. Animal models are crucial to help investigators reveal the mechanisms underlying these disorders. Murine models are used most commonly. Rats are the better subject in dental implant research, due to mice could not provide clinical compatible and macro-level measurable data for implant osseointegration and peri-implantitis in oral cavity for lacking enough cancellous bone to support an implant more than 1 mm in length. Objective Our aim of this research is to find a clinical comparable rat dental implant model. Methods Six male Sprague-Dawley rats with body weight more than 500 g were used in the experiment. Each rat received two implants. One implant was placed at maxillary diastema in each side. Seven weeks after the implantation, only one implant successfully osseointegrated without movement and inflammation. Implant success and failure rate is analyzed by using Clopper-Pearson's exact method at 95% confidence interval. Results The present data indicate that the true success rate of implantation in maxillary natural diastema in rat is less than 38.4% at a confident level of 95%. Meanwhile, Micro-CT indicates maxillary first molar position will be a promising site for implantation. Conclusion Maxillary nature diastema may not be an appropriate site for implantation research for its low successful rate, but maxillary first molar position could be a candidate for implantation research. Further researches are required to illustrate the details.